Conflitos e resistências de professores primários paulistas indiciados por processos disciplinares (1890-1906) - Cunha, Tiago Donizette da (2020)
The research analyzed the performance of primary teachers in the first republican years, specifically those who taught in the state of São Paulo between the years 1890 to 1906, a period characterized by the coexistence of graduated and non-graduated schools, in addition to the expansion and circulation of teachers in these institutions education. We opted for a selection of subjects that gained prominence in the disciplinary proceedings filed against teachers and in the semiannual reports prepared by teachers, inspectors and principals. These documents presented information about the material situation of the schools, the professional and personal conditions of the teachers, as well as the arguments of accusations and allegations of defense of the teachers during the inquiries listed. In view of the questions raised, the initial procedure was to map the performance of certain primary teachers in the cities of São Paulo who demonstrated in their daily actions resistance and negotiations to prescribed and non-prescribed educational norms. This meant, in practice, to analyze especially disciplinary proceedings against primary school teachers, as well as the reports produced by teachers, inspectors and principals in the school routine. The main objective was to ascertain the prescribed and non-prescribed motivations for opening disciplinary proceedings, in addition to comparing the actions of those involved with the working conditions and with the political circumstances of the regions or cities where they operated. With that, it was possible to evaluate how the State's disciplinary rules were used in social contexts of tensions, conflicts and alliances involving teachers, directors, inspectors and local authorities. It is considered that, for the period circumscribed by the research, the disciplinary processes represented the denotation of a movement of the State of São Paulo in effectively incorporating the figure of the teacher as a civil servant, punishing those who deviated from bureaucratic or moral norms. Simultaneously, whether designed or not for this purpose, these interferences in the teachers' lives gained the political connotation of instruments of control, resistance, promotion, persecution or dismissal, given the coronelista conjunctures